5G Opportunities for Future Technology - Abram Sanggel; Julianus Gesuri Daud; Rinna Yuanita Kasenda; Leony Ariesta Wenno; Yonatan Tampi; Cisilia Masambe; Jeremy Tinggogoy; Wahyu Rumerung; Rivaldo Karenting (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
5G technology is the next generation mobile phone technology and offers a significant opportunity for future technological developments. Against this background, we will discuss some of the key opportunities that 5G provides for future technological development. First, 5G provides unprecedented speed and communication quality. Second, the Internet of Things (IoT) will achieve rapid growth through 5G. Third, the advantages of 5G  make our job easier. High-quality 4K video conferencing and instant collaboration become easier, making workdays more productive. Fourth, 5G also has significant potential in the healthcare field. Telemedicine will become more effective and more accessible and will provide better and more affordable care anytime and anywhere. Furthermore, 5G technology will enable remote patient monitoring, improving chronic disease management and overall healthcare management. Lastly, security is also a goal in the development of 5G technology. With increased connectivity capacity, data protection and privacy have become more important than ever. To maximize the benefits of implementing 5G, it is important to create a safe and reliable cybersecurity environment. Overall, 5G technology opens up new opportunities in various fields, including entertainment, transportation, and healthcare. The future of technology looks bright as infrastructure and other applications continue to improve.